Organic electrolyte solution and lithium battery comprising the same
By using the used electrolyte solution of fluorophosphate compounds in lithium batteries and lithium transition metal oxide positive active materials with high nickel content, the problem of stability and deterioration of lithium batteries in the filling cycle is solved, and the battery life extension is achieved And the decrease in internal resistance.
Patent Information
- Application Number
- CN201811541470.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-12-27
- Filing Date
- 2018-12-17
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2038-12-17
AI Technical Summary
There is a side reaction between the positive electrode active material and the electrolyte during the charging/discharging cycle of lithium secondary batteries, resulting in deterioration of battery stability.
The electrolytic solution containing lithium salt, organic solvents and fluorophosphate compounds is used, and nickel -transitioned metal oxides with nickel and transition metals are used in positive active materials. The nickel content is about 70 percentage or larger.
By inhibiting the elution and side reactions of transition metals, improve the life characteristics of lithium batteries, reduce internal resistance, and inhibit gas generation, extend the cycle life of the battery.
Smart Images

Figure CN110010967B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2017-0181517 filed in the Korean Intellectual Property Office on December 27, 2017 and all rights arising therefrom, the contents of which are incorporated herein in their entirety by reference. Technical Field
[0003] The present disclosure relates to an organic electrolyte solution and a lithium battery including the same. Background Art
[0004] Lithium secondary batteries are used as driving sources for portable electronic devices such as video cameras, mobile phones, and laptop computers. Lithium secondary batteries are rechargeable at high rates and have a specific energy that is about three times higher than that of lead batteries, nickel-cadmium (Ni-Cd) batteries, nickel-hydrogen batteries, or nickel-zinc batteries.
[0005] Positive electrode active materials with increased discharge capacity can be used to manufacture lithium ion secondary batteries with high energy density. However, the positive electrode active materials with increased discharge capacity may also have relatively low electrochemical stability. Therefore, side reactions between the positive electrode active materials and the electrolyte may occur during the charge / discharge of the lithium secondary battery, and thus the stability of the lithium secondary battery deteriorates in continuous charge / discharge cycles. Therefore, it would be desirable to provide an improved lithium secondary battery by including a positive electrode active material with increased discharge capacity and increased electrochemical stability. Summary of the invention
[0006] Provided are a novel organic electrolyte solution and a lithium battery comprising the same.
[0007] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description, or may be learned by practice of the presented embodiments.
[0008] According to one aspect of an embodiment, an organic electrolyte solution includes: a lithium salt; an organic solvent; and a fluorine-containing phosphate compound, wherein the fluorine-containing phosphate compound is represented by Formula 1:
[0009]
[0010]
[0011] In formula 1,
[0012] R 1 , R 2 , R 3 , R 4 , R5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , and R 15 each independently represents a hydrogen atom, a fluorine atom, a C1-C5 alkyl group which may be substituted by a halogen atom, a C4-C10 cycloalkyl group which may be substituted by a halogen atom, a C6-C10 aryl group which may be substituted by a halogen atom, a C2-C10 heteroaryl group which may be substituted by a halogen atom, or a C2-C10 alkenyl group which may be substituted by a halogen atom,
[0013] R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , and R 15 is a fluorine atom, and
[0014] At least one phenyl group has no fluorine atom.
[0015] According to another aspect of the embodiment, a lithium battery includes: a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; and the organic electrolyte solution between the positive electrode and the negative electrode, wherein the positive electrode active material includes a lithium transition metal oxide containing nickel and at least one transition metal other than nickel, and wherein the amount of nickel in the lithium transition metal oxide is about 80 mole percent (mol %) or greater, based on the total moles of the transition metal. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] These and / or other aspects will become apparent and more readily appreciated from the following description of the embodiments considered in conjunction with the accompanying drawings, in which:
[0017] Figure 1 is a schematic diagram of a lithium battery according to an example embodiment. DETAILED DESCRIPTION
[0018] The embodiments will now be described in detail with reference to the accompanying drawings in which various embodiments are shown. The same reference numerals always represent the same elements. In this regard, the embodiments may have different forms and should not be construed as being limited to the description set forth herein. Therefore, the embodiments are described below only by reference to the accompanying drawings to illustrate various aspects.
[0019] The terms used herein are only for the purpose of describing specific embodiments and are not intended to be restrictive. As used herein, the singular forms "a (a, an)" and "the (said)" are intended to include plural forms, including "at least one (a)", unless the content clearly indicates otherwise. For example, "substituted by fluorine atoms" includes being replaced by one, two, three or more fluorine atoms. "At least one (a)" should not be interpreted as limiting "a (a)". "Or" means "and / or". As used herein, the term "and / or" includes any and all combinations of one or more of the relevant listed items. Expressions such as "at least one (a) of..." modify the entire list of elements when before or after the list of elements, rather than modifying the individual elements of the list.
[0020] Hereinafter, because the inventive concept allows for multiple variations and many embodiments, specific embodiments will be shown in the drawings and described in detail in the written description. However, this is not intended to limit the inventive concept to a specific practice mode, and it will be appreciated that all variations, equivalents and substitutes that do not deviate from the spirit and technical scope are included in the inventive concept.
[0021] The terms used herein are only used to describe specific embodiments and are not intended to limit the inventive concept. Expressions used in the singular include expressions in the plural, unless they have a significantly different meaning in the context. As used herein, it will be understood that terms such as "include", "have" and "comprise" are intended to indicate the presence of features, quantities, steps, actions, components, parts, ingredients, materials, or combinations thereof disclosed in the specification, but do not exclude the possibility that one or more additional features, quantities, steps, actions, components, parts, ingredients, materials, or combinations thereof may exist or may be added. The symbol " / " used herein may be interpreted as "and" or "or" depending on the context.
[0022] In the drawings, for the sake of clarity, the diameter, length and thickness of layers and regions are enlarged or reduced. Throughout the specification, it will be understood that when a component such as a layer, film, region or plate is referred to as "on" another component, the component may be directly on the other component, or there may be an intermediate component thereon. On the contrary, when an element is referred to as "directly on" another element, there is no intermediate element. Throughout the specification, although terms such as "first", "second" and the like can be used to describe various components, such components should not be limited to the above terms. The above terms are only used to distinguish a component from another component. In order to better understand the features of the present invention, some components may not be shown in the drawings, but it is not intended to omit the components.
[0023] As used herein, "about" or "approximately" is inclusive of the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations of the stated value, such as within ±20%, 10%, or 5%.
[0024] Unless otherwise defined, all terms (including technical and scientific terms) used in this article have the same meaning as commonly understood by ordinary technicians in the field to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and the present disclosure, and will not be interpreted in an idealized or excessive formal sense unless clearly defined in this article.
[0025] Hereinafter, according to example embodiments, an organic electrolyte solution and a lithium battery including the same will be described.
[0026] According to one embodiment, the organic electrolyte solution includes: a lithium salt; an organic solvent; and a fluorine-containing phosphate compound represented by Formula 1:
[0027]
[0028] In formula 1, R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14, and R 15 are each independently a hydrogen atom, a fluorine atom, a C1-C5 alkyl group which may be substituted by a halogen atom, a C4-C10 cycloalkyl group which may be substituted by a halogen atom, a C6-C10 aryl group which may be substituted by a halogen atom, a C2-C10 heteroaryl group which may be substituted by a halogen atom, or a C2-C10 alkenyl group which may be substituted by a halogen atom, R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , and R 15 At least one of the phenyl groups is a fluorine atom, and at least one of the phenyl groups does not have a fluorine atom (ie, does not contain fluorine).
[0029] In an embodiment, in Formula 1, R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , and R 15 are each independently a hydrogen atom, a fluorine atom, a C1-C5 alkyl group which may be substituted by a fluorine atom, a C4-C10 cycloalkyl group which may be substituted by a fluorine atom, a C6-C10 aryl group which may be substituted by a fluorine atom, a C2-C10 heteroaryl group which may be substituted by a fluorine atom, or a C2-C10 alkenyl group which may be substituted by a fluorine atom; R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , and R 15at least one of the phenyl groups is a fluorine atom; and at least one of the phenyl groups does not contain fluorine (ie, does not have a fluorine atom, or in other words, is not substituted by any fluorine atom).
[0030] Without being bound by theory, it is believed that the fluorine-containing phosphate compound represented by Formula 1 and including a phenyl group that is not substituted by fluorine (also referred to herein as a fluorine-containing phosphate-based compound) is stably bonded or coordinated with the transition metal of the lithium transition metal oxide used as a positive electrode active material, and thus can act as a scavenger of protons retained in the organic electrolyte solution. Therefore, the fluorine-containing phosphate compound represented by Formula 1 can inhibit the elution of transition metals from the positive electrode active material in contact with the organic electrolyte solution and can inhibit the side reaction of the organic electrolyte solution. As a result, the life characteristics of a lithium battery including an organic electrolyte solution containing a fluorine-containing phosphate compound represented by Formula 1 can be improved, and the gas generated by the side reaction with the electrolyte can be suppressed. Again without being limited by theory, it is understood that when a fluorine-containing phosphate compound represented by Formula 1 is used, oxidation at high voltage can be suppressed, and therefore the fluorine-containing phosphate compound represented by Formula 1 is retained in the positive electrode for a long time after charge / discharge, and as a result, the degradation of the lithium battery can be prevented. When the fluorine-containing phosphate compound represented by Formula 1 has an asymmetric structure, i.e., includes at least one unsubstituted phenyl group, the fluorine-containing phosphate compound represented by Formula 1 can provide improved life characteristics and reduced internal resistance compared to a fluorine-containing phosphate-based compound having a symmetrical structure (i.e., wherein all phenyl groups contain at least one fluorine atom). In some embodiments, the organic electrolyte solution may not include a fluorine-containing phosphate compound having a symmetrical structure.
[0031] In the organic electrolyte solution, the amount of the fluorine-containing phosphate-based compound represented by Formula 1 may be, for example, 10 weight percent (wt%) or less, 8 weight percent or less, 5 weight percent or less, 4 weight percent or less, 3 weight percent or less, 2 weight percent or less, 1.5 weight percent or less, or 1 weight percent or less, based on the total weight of the organic electrolyte solution, provided that there is an amount of the fluorine-containing phosphate-based compound represented by Formula 1. In the organic electrolyte solution, the amount of the fluorine-containing phosphate-based compound represented by Formula 1 may be, for example, in the range of about 0.01 weight percent to about 10 weight percent, about 0.01 weight percent to about 8 weight percent, about 0.01 weight percent to about 5 weight percent, about 0.01 weight percent to about 4 weight percent, about 0.01 weight percent to about 3 weight percent, about 0.01 weight percent to about 2 weight percent, about 0.01 weight percent to about 1.5 weight percent, or about 0.01 weight percent to about 1 weight percent, based on the total weight of the organic electrolyte solution. For example, in the organic electrolyte solution, the amount of the fluorine-containing phosphate-based compound represented by Formula 1 is in the range of about 0.1 wt % to about 2 wt % based on the total weight of the organic electrolyte solution.
[0032] In the organic electrolyte solution, the fluorine-containing phosphate-based compound represented by Formula 1 may be, for example, a fluorine-containing phosphate-based compound represented by at least one of Formula 2 or Formula 3:
[0033]
[0034] In equations 2 and 3, R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , and R 10 are each independently a hydrogen atom, a fluorine atom, a C1-C5 alkyl group which may be substituted by a fluorine atom, a C4-C10 cycloalkyl group which may be substituted by a fluorine atom, a C6-C10 aryl group which may be substituted by a fluorine atom, a C2-C10 heteroaryl group which may be substituted by a fluorine atom, or a C2-C10 alkenyl group which may be substituted by a fluorine atom; and R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , or R 10 At least one of them is a fluorine atom.
[0035] In the organic electrolyte solution, the fluorine-containing phosphate-based compound represented by Formula 1 may be, for example, a compound represented by at least one of Formula 4 to Formula 9:
[0036]
[0037] In the organic electrolyte solution, the fluorine-containing phosphate-based compound represented by Formula 1 may be, for example, a compound represented by at least one of Formulas 10-15.
[0038]
[0039] In the organic electrolyte solution, the amount of the fluorine-containing phosphate-based compound represented by Formula 1 may be in the range of about 0.001 wt % to about 2 wt %, about 0.01 wt % to about 2 wt %, about 0.1 wt % to about 2 wt %, or about 0.5 wt % to about 2 wt %, based on the total weight of the organic electrolyte solution. When the amount of the fluorine-containing phosphate-based compound represented by Formula 1 is within these ranges, the lithium battery may have excellent life characteristics. Therefore, gas generation can be suppressed without significant changes in life characteristics. When the amount of the fluorine-containing phosphate-based compound represented by Formula 1 is too small, the improvement in the life characteristics of the lithium battery is negligible, and when the amount of the fluorine-containing phosphate-based compound represented by Formula 1 is too large, the high rate characteristics of the lithium battery may be degraded.
[0040] The organic electrolyte solution according to the embodiment may further include at least one compound represented by Formula 16 to Formula 21:
[0041]
[0042] In formula 16-21, X 1 , X 2 , X 3 , X 4 , X 5 , X 6 , X 7 , X 8 , X 9 , X 10 , X 11 , X 12 , and X 13 are each independently a hydrogen atom or a halogen atom, and X 1 and X 2 At least one of them is a fluorine atom (F).
[0043] When the organic electrolyte solution further includes a cyclic carbonate compound represented by Formula 16, the life characteristics and resistance suppression effect of the lithium battery can be further improved. For example, in the cyclic carbonate compound represented by Formula 16, X 1 is a hydrogen atom, and X 2 For F.
[0044] The amount of the cyclic carbonate compound represented by formula 16 can be, for example, 10 volume percents (volume %) or less, 9 volume % or less, 8 volume % or less, 7 volume % or less, 6 volume % or less or 5 volume % or less, based on the cumulative volume of the organic solvent. In some embodiments, when present, the cyclic carbonate compound represented by formula 16 can be up to 10 volume %, up to 9 volume %, up to 8 volume %, up to 7 volume %, up to 6 volume % or up to 5 volume % in an amount present, based on the cumulative volume of the organic solvent. The amount of the cyclic carbonate compound represented by formula 16 can be in the range of about 0.1 volume % to about 10 volume %, about 0.1 volume % to about 9 volume %, about 0.1 volume % to about 8 volume %, about 0.1 volume % to about 7 volume %, about 0.1 volume % to about 6 volume % or about 0.1 volume % to about 5 volume %, based on the cumulative volume of the organic solvent. When the amount of the cyclic carbonate compound represented by Formula 16 is within these ranges, the lifespan characteristics and resistance suppression effect of the lithium battery may be further improved.
[0045] When the organic electrolyte solution further includes a cyclic carbonate compound represented by Formula 17 and / or Formula 18, the life characteristics and resistance suppression effect of the lithium battery can be further improved. For example, in the cyclic carbonate compound represented by Formula 17 and / or Formula 18, X 3 , X 4 and X 5 All may be hydrogen. The amount of each cyclic carbonate compound represented by Formula 17 and / or Formula 18 may be, for example, 3 wt % or less, 2.5 wt % or less, 2 wt % or less, or 1.5 wt % or less, based on the gross weight of the organic electrolyte solution. The amount of each cyclic carbonate compound represented by Formula 17 and / or Formula 18 may be, for example, up to 3 wt %, up to 2.5 wt %, up to 2 wt %, or up to 1.5 wt %, based on the gross weight of the organic electrolyte solution. The amount of the cyclic carbonate compound represented by Formula 17 and / or Formula 18 may be, for example, in the range of about 0.1 wt % to about 3 wt %, about 0.1 wt % to about 2.5 wt %, about 0.1 wt % to about 2 wt %, or about 0.1 wt % to about 1.5 wt %, based on the gross weight of the organic electrolyte solution. When the amount of the cyclic carbonate compound represented by Formula 17 and / or Formula 18 is within these ranges, the life characteristics and resistance suppression effect of the lithium battery may be further improved.
[0046] When the organic electrolyte solution further includes a cyclic anhydride compound represented by Formula 19 and / or Formula 20, the cycle characteristics of the lithium battery can be further improved. For example, in the cyclic anhydride compound represented by Formula 19 and / or Formula 20, X 6 , X7 , X 8 and X 9 It may be hydrogen. The amount of the cyclic anhydride compound represented by Formula 19 and / or Formula 20 may be, for example, 3 wt % or less, 2.5 wt % or less, 2 wt % or less, or 1.5 wt % or less, based on the total weight of the organic electrolyte solution. The amount of the cyclic anhydride compound represented by Formula 19 and / or Formula 20 may be, for example, up to 3 wt %, or up to 2.5 wt %, or up to 2 wt %, or up to 1.5 wt %, based on the total weight of the organic electrolyte solution. The amount of the cyclic anhydride compound represented by Formula 19 and / or Formula 20 may be, for example, in the range of about 0.1 wt % to about 3 wt %, about 0.1 wt % to about 2.5 wt %, about 0.1 wt % to about 2 wt %, or about 0.1 wt % to about 1.5 wt %, based on the total weight of the organic electrolyte solution. When the amount of the cyclic anhydride compound represented by Formula 19 and / or Formula 20 is within these ranges, the cycle characteristics of the lithium battery may be further improved.
[0047] When the organic electrolyte solution further includes a cyclic disulfonate compound represented by Formula 21, the cycle characteristics of the lithium battery can be further improved. For example, in the cyclic disulfonate compound represented by Formula 21, X 10 , X 11 , X 12 and X 13 It may be hydrogen.
[0048] The amount of the cyclic disulfonate compound represented by Formula 21 may be, for example, 3 wt % or less, 2.5 wt % or less, 2.0 wt % or less, or 1.5 wt % or less, based on the total weight of the organic electrolyte solution. The amount of the cyclic disulfonate compound represented by Formula 21 may be, for example, up to 3 wt %, or up to 2.5 wt %, or up to 2 wt %, or up to 1.5 wt %, based on the total weight of the organic electrolyte solution. The amount of the cyclic disulfonate compound represented by Formula 21 may be, for example, in the range of about 0.1 wt % to about 3 wt %, about 0.1 wt % to about 2.5 wt %, about 0.1 wt % to about 2 wt %, or about 0.1 wt % to about 1.5 wt %, based on the total weight of the organic electrolyte solution. When the amount of the cyclic disulfonate compound represented by Formula 21 is within these ranges, the cycle characteristics of the lithium battery may be further improved.
[0049] The organic solvent may, for example, include at least one of a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, and a nitrile solvent.
[0050] Examples of the carbonate solvent may include carbonate-based solvents such as ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), propylene carbonate (PC), ethylene carbonate (EC), or butylene carbonate (BC); examples of the ester solvent may include ester-based solvents such as methyl propionate, ethyl propionate, ethyl butyrate, methyl acetate, ethyl acetate, n-propyl acetate, Ester, tert-butyl acetate, γ-butyrolactone, decanoic acid ester, γ-valerolactone, decanoic acid ester, γ-valerolactone, mevalonolactone or caprolactone; Examples of the ether solvent include ether-based solvents such as dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran, or a combination thereof; and Examples of the ketone solvent include ketone-based solvents such as cyclohexanone; Examples of the nitrile solvent include nitrile-based solvents such as acetonitrile (AN), succinonitrile (SN), or adiponitrile, but embodiments are not limited thereto. Examples of other solvents that can be used include dimethyl sulfoxide, dimethylformamide and dimethylacetamide, but embodiments are not limited thereto. A combination of at least two of the aforementioned solvents may also be used.
[0051] For example, the organic solvent can be the solvent mixture comprising the chain-type (that is, non-cyclic) carbonate of about 50 volume % to about 95 volume % and the cyclic carbonate of about 5 volume % to about 50 volume % or the chain-type carbonate of about 55 volume % to about 95 volume % and the cyclic carbonate of about 5 volume % to about 45 volume % or the chain-type carbonate of about 60 volume % to about 95 volume % and the cyclic carbonate of about 5 volume % to about 40 volume % or the chain-type carbonate of about 65 volume % to about 95 volume % and the cyclic carbonate of about 5 volume % to about 35 volume % or the chain-type carbonate of about 70 volume % to about 95 volume % and the cyclic carbonate of about 5 volume % to about 30 volume %.For example, the organic solvent is the solvent mixture comprising at least three organic solvents.
[0052] For example, the organic electrolyte solution may include about 0.01 wt % to about 2.0 wt % of a fluorine-containing phosphate-based compound represented by one of Formulas 4 to 15, about 0.1 wt % to about 2.0 wt % of a compound represented by Formula 17a, about 0.1 wt % to about 1.0 wt % of a compound represented by Formula 19a, and about 0.1 wt % to about 1.0 wt % of a compound represented by Formula 21a, wherein the weight percentages are based on the total weight of the organic electrolyte solution, and the organic solvent includes about 1 volume % to about 10 volume % of a compound represented by Formula 16a, based on the total volume of the organic solvent:
[0053]
[0054]
[0055] The lithium salt may include at least one of the following: LiPF 6 , LiBF 4 、LiCF 3 SO 3 、Li(CF 3 SO 2 ) 2 N, LiC 2 F 5 SO 3 、Li(FSO 2 ) 2 N, LiC 4 F 9 SO 3 、LiN(SO 2 CF 2 CF 3 ) 2 , or a compound represented by Formula 30 to Formula 33, but the embodiment is not limited thereto, and any material that can be used as a lithium salt in the art may be used.
[0056]
[0057] The organic electrolyte solution according to the embodiment may not include LiFSI.
[0058] The concentration of the lithium salt included in the organic electrolyte solution may be in the range of about 0.01 molar concentration (M) to about 5.0 M, or about 0.05 M to about 5.0 M, about 0.1 M to about 5.0 M, or about 0.1 M to about 2.0 M, but the embodiment is not limited thereto, and the concentration of the lithium salt may be changed as needed. When the concentration of the lithium salt is within the above range, battery characteristics may be further improved.
[0059] According to another embodiment, a lithium battery includes: a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; and the organic electrolyte solution between the positive electrode and the negative electrode, wherein the positive electrode active material includes a lithium transition metal oxide containing nickel and at least one transition metal other than nickel, and the amount of nickel in the lithium transition metal oxide is about 70 mole percent (mol %) or greater, based on the total moles of the transition metal.
[0060] When the positive electrode active material is a lithium transition metal oxide containing nickel and a transition metal other than nickel, and the amount of nickel in the lithium transition metal oxide is 70 mol% or more, a lithium battery with high output and high capacity can be manufactured. Without being limited by theory, it is understood that when a lithium transition metal oxide with a high nickel content is included in a lithium battery, the surface structure of the lithium transition metal oxide may be unstable, gas generation caused by side reactions may occur during charging / discharging of the battery, and the elution of transition metals such as nickel may be enhanced. Therefore, the life characteristics of the lithium battery may deteriorate. On the other hand, a lithium battery including a fluorophosphoric acid ester compound according to an embodiment has improved characteristics. In particular, when the lithium battery includes an electrolyte solution (based on the total weight of the organic electrolyte solution) containing the fluorophosphoric acid ester-based compound having a phenyl group not substituted by fluorine in an amount of about 2 wt% or less, the lithium battery may have improved life characteristics and a reduced internal resistance, which can suppress gas generation caused by side reactions.
[0061] The positive electrode active material includes a lithium transition metal oxide containing nickel and at least one transition metal other than nickel. In the lithium transition metal oxide, the amount of nickel may be about 70 mol% or more, or about 80 mol% or more, or about 82 mol% or more, or about 85 mol% or more, or about 87 mol% or more, or about 90 mol% or more, based on the total number of moles of transition metals.
[0062] For example, the lithium transition metal oxide may be a compound represented by Formula 23:
[0063] Formula 23
[0064] Li a Ni x Co y M z O 2-b A b
[0065] In Formula 23, 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.7 ≤ x < 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z = 1; M is at least one of manganese (Mn), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), or boron (B); and A is F, S, Cl, Br, or a combination thereof. For example, 0.83 ≤ x < 0.97, 0 < y ≤ 0.15, 0 < z ≤ 0.15, and x + y + z = 1; or 0.85 ≤ x < 0.95, 0 < y ≤ 0.1, 0 < z ≤ 0.1, and x + y + z = 1.
[0066] For example, the lithium transition metal oxide may be a compound represented by one of Formulas 24 and 25:
[0067] Formula 24
[0068] LiNi x Co y Mn z O 2
[0069] Formula 25
[0070] LiNi x Co y Al z O 2
[0071] In Formulas 24 and 25, 0.7 ≤ x ≤ 0.95, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z = 1. For example, 0.8 ≤ x ≤ 0.95, 0 < y ≤ 0.2, 0 < z ≤ 0.2, and x + y + z = 1. For example, 0.82 ≤ x ≤ 0.95, 0 < y ≤ 0.15, 0 < z ≤ 0.15, and x + y + z = 1. For example, 0.85 ≤ x ≤ 0.95, 0 < y ≤ 0.1, 0 < z ≤ 0.1, and x + y + z = 1.
[0072] The lithium transition metal oxide may include, for example, LiNi 0.7 Co 0.2 Mn 0.1 O 2 , LiNi 0.88 Co 0.08 Mn 0.04 O 2 , LiNi 0.8 Co 0.15 Mn 0.05 O 2 , LiNi 0.8 Co 0.1 Mn 0.1 O 2 , LiNi 0.88 Co 0.1 Mn 0.02 O 2 , LiNi 0.8 Co 0.15 Al 0.05 O 2 , LiNi 0.8 Co 0.1 Al 0.1 O 2 , LiNi 0.88 Co 0.1 Al 0.02 O 2 , or a combination thereof.
[0073] The negative electrode active material may include at least one of the following: a silicon-based material, a carbon-based material, a composite of a silicon-based material and a carbon-based material, or a silicon oxide (SiO x , where 0 < x < 2). For example, the silicon-based material may be silicon nanoparticles. For example, the carbon-based material may be graphite.
[0074] For example, the composite of the silicon-based material and the carbon-based material may include silicon nanoparticles. For example, the composite of the silicon-based material and the carbon-based material may be a composite having a structure in which silicon nanoparticles are disposed (e.g., coated) on the carbon-based material, a composite having a structure in which silicon particles are disposed on and inside the carbon-based material, or a composite having a structure in which silicon particles are coated with the carbon-based material. For example, the composite of the silicon-based material and the carbon-based material may be an active material obtained by dispersing silicon nanoparticles having a particle size of about 200 nanometers (nm) or less on carbon-based material particles and then carbon-coating the silicon nanoparticles. For example, the composite of the silicon-based material and the carbon-based material may be an active material having silicon (Si) particles disposed on and inside graphite.
[0075] As used herein, the term "size" or "particle size" means the average diameter when the particle is spherical or the average length scale such as along the major surface when the particle is non-spherical. For example, the size of the particles can be measured by using a particle size analyzer (PSA).
[0076] For example, the particle size (e.g., the secondary particle size) of the composite of the silicon-based material and the carbon-based material may be in the range of about 5 micrometers (μm) to about 20 μm, or about 5 μm to about 18 μm, or about 7 μm to about 18 μm, or about 7 μm to about 15 μm, or about 10 μm to about 13 μm. For example, the particle size of the composite of the silicon-based material and the carbon-based material may be the secondary particle size (average diameter). For example, the size of the silicon nanoparticles may be the primary particle size and may be 5 nm or greater, or 10 nm or greater, or 20 nm or greater, or 50 nm or greater, or 70 nm or greater. For example, the size of the silicon nanoparticles may be 300 nm or less, or 200 nm or less, or 150 nm or less, or 100 nm or less, or 50 nm or less, or 20 nm or less, or 10 nm or less. For example, the size of the silicon nanoparticles may be in the range of about 10 nm to about 250 nm. For example, the size of the silicon nanoparticles may be the average diameter.
[0077] For example, the capacity retention rate of the lithium battery at 45° C. may be about 70% or more, about 75% or more, or about 78% or more, as measured after 200 charge / discharge cycles. For example, the increase rate of the direct current internal resistance (DCIR) of the lithium battery at 45° C. may be about 20% or less, about 18% or less, about 15% or less, about 12% or less, about 10% or less, or about 5% or less, or in the range of about 5% to about 20%, as measured after 200 charge / discharge cycles. When the lithium battery has excellent capacity retention and low DCIR increase rate after 200 cycles at 45° C., the cycle characteristics of the lithium battery may be improved.
[0078] For example, the energy density per unit cell unit volume of the lithium battery may be about 500 watt-hours / liter (Wh / L) or more, about 550Wh / L or more, about 600Wh / L or more, about 650Wh / L or more, or about 700Wh / L or more. When the lithium battery has a high energy density of about 500Wh / L or more, the lithium battery may have a high output.
[0079] The type of the lithium battery is not particularly limited, and the lithium battery may be a lithium ion battery, a lithium ion polymer battery, or a lithium sulfur battery.
[0080] In some embodiments, the lithium battery can be manufactured as follows.
[0081] First, prepare the positive electrode.
[0082] For example, a positive electrode active material, a conductive agent, a binder, and a solvent are mixed to prepare a positive electrode active material composition. In some embodiments, the positive electrode active material composition may be directly coated on a positive electrode current collector to prepare a positive electrode plate. In some embodiments, the positive electrode active material composition may be cast on a separate carrier to form a positive electrode active material film, which may then be separated from the carrier and laminated on a positive electrode current collector to prepare a positive electrode plate. The positive electrode is not limited to the above examples and may be one of a variety of types.
[0083] In addition to nickel-rich lithium-nickel composite oxides (i.e., lithium transition metal oxides containing nickel and at least one transition metal other than nickel, and the amount of nickel in the lithium transition metal oxide is about 70 mole percent (mol%) or more, based on the total moles of transition metals), ordinary (usual) lithium-containing metal oxides can be used together as positive electrode active materials. In some embodiments, the lithium-containing metal oxide may be at least two of a composite oxide of lithium and a metal including Co, Mn, Ni, or a combination thereof. In some embodiments, the positive electrode active material may further include a compound represented by one of the following formulas:
[0084] Li a A 1-b B' b D' 2 (where 0.90≤a≤1.8 and 0≤b≤0.5); Li a E 1-b B' b O 2-c D' c (where 0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); LiE 2-b B' b O 4-c D' c (where 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b- c Co b B' c D' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Co b B' c O 2-α F' 2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c D' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Mn b B' c O 2-α F' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c O 2-α F' 2(where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni b E c G d O 2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, and 0.001≤d≤0.1.); Li a Ni b Co c Mn d G e O 2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0.001≤e≤0.1.); Li a NeG b O 2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1.); Li a CoG b O 2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1.); Li a MnG b O 2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1.); Li a Mn 2 G b O 4 (where 0.90≤a≤1.8 and 0.001≤b≤0.1.); QO 2 ;QS 2 ;LiQS 2 ; V 2 O 5 ;LiV 2 O 5 ;LiI'O 2 ;LiNiVO 4 ;Li (3-f) J 2 (PO 4 ) 3 (where 0≤f≤2); Li (3-f) Fe 2 (PO 4 ) 3 (where 0≤f≤2); and LiFePO 4 .
[0085] In the above formula, A may include nickel (Ni), cobalt (Co), manganese (Mn), or a combination thereof; B' may include aluminum (Al), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), iron (Fe), magnesium (Mg), strontium (Sr), vanadium (V), rare earth elements, or a combination thereof; D' may include oxygen (O), fluorine (F), sulfur (S), phosphorus (P), or a combination thereof; E may include cobalt (Co), manganese (Mn), or a combination thereof; F' may include fluorine (F), sulfur (S), phosphorus (P), or a combination thereof alloy; G may include aluminum (Al), chromium (Cr), manganese (Mn), iron (Fe), magnesium (Mg), lanthanum (La), cerium (Ce), strontium (Sr), vanadium (V), or a combination thereof; Q may include titanium (Ti), molybdenum (Mo), manganese (Mn), or a combination thereof; I' may include chromium (Cr), vanadium (V), iron (Fe), scandium (Sc), yttrium (Y), or a combination thereof; and J may include vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), nickel (Ni), copper (Cu), or a combination thereof.
[0086] The compound listed above as the positive electrode active material may be a composite having a coating layer on the surface of the above-listed compound, or may be a mixture of a compound having no coating layer and a compound having a coating layer, the compound being at least one of the above-listed compounds.
[0087] In some embodiments, the coating layer may include at least one compound of the coating element, including, for example, oxides, hydroxides, oxyhydroxides, oxycarbonates, or hydroxycarbonates of the coating element. In some embodiments, the compound for the coating layer may be amorphous or crystalline. In some embodiments, the coating element for the coating layer may include magnesium (Mg), aluminum (Al), cobalt (Co), potassium (K), sodium (Na), calcium (Ca), silicon (Si), titanium (Ti), vanadium (V), tin (Sn), germanium (Ge), gallium (Ga), boron (B), arsenic (As), zirconium (Zr), or a combination thereof. In some embodiments, the coating layer may be formed using any method that does not adversely affect the physical properties of the positive active material. For example, the coating layer may be formed using a spraying method or an impregnation method. The coating method is well known to those of ordinary skill in the art, and therefore a detailed description thereof is omitted.
[0088] In some embodiments, the positive electrode active material may further include, for example, LiNiO 2 、LiCoO 2 、LiMn x O 2x (where x = 1 or 2), LiNi 1-x Mn x O 2 (where 0 <x<1)、LiNi 1-x-y Cox Mn y O 2 (where 0≤x≤0.5 and 0≤y≤0.5), LiFePO 4 , or a combination thereof.
[0089] As the conductive agent, any suitable material can be used as long as it has conductivity and does not cause chemical changes in the lithium battery. Examples of the conductive agent include: graphite such as natural graphite or artificial graphite; carbonaceous materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or summer black; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum powder or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; and conductive polymers such as polyphenylene derivatives. A combination of at least two of the aforementioned conductive agents may also be used. The amount of the conductive agent may be in the range of about 1 wt % to about 20 wt %, or about 2 wt % to about 18 wt %, or about 5 wt % to about 15 wt %, based on the total weight of the positive active material composition.
[0090] The binder in the positive electrode active material composition is a component that helps the bonding between the positive electrode active material and the additive (such as a conductive agent) or the bonding between the current collector and the positive electrode active material. Examples of the binder include polyvinylidene fluoride (PVdF), polyvinylidene chloride, polybenzimidazole, polyimide, polyvinyl acetate, polyacrylonitrile, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polyethylene, polypropylene, polystyrene, polymethyl methacrylate, polyaniline, acrylonitrile butadiene styrene copolymer, phenolic resin, epoxy resin, polyethylene terephthalate, polytetrafluoroethylene, polyphenylene sulfide, polyamideimide, polyetherimide, polyethersulfone, polyamide, polyacetal, polyphenylene oxide, polybutylene terephthalate, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or a plurality of copolymers thereof, or a combination thereof, but embodiments are not limited thereto. For example, the amount of the binder may be in the range of about 1 wt % to about 30 wt %, or about 2 wt % to about 25 wt %, or about 5 wt % to about 20 wt %, based on the total weight of the positive active material composition.
[0091] Examples of the solvent include N-methyl-pyrrolidone, acetone, water, or a combination thereof, but embodiments are not limited thereto. Any material suitable for use as a solvent may be used. The amount of the solvent may be, for example, in the range of about 10 parts by weight to about 100 parts by weight, or about 15 parts by weight to about 100 parts by weight, or about 20 parts by weight to about 85 parts by weight, based on 100 parts by weight of the positive electrode active material. When the amount of the solvent is within the above range, a positive electrode active material layer can be easily formed.
[0092] The amounts of the positive electrode active material, the conductive agent, the binder and the solvent can be determined by those skilled in the art without undue experimentation. Depending on the desired use and structure of the lithium battery, at least one of the conductive agent, the binder and the solvent may be omitted.
[0093] In the positive electrode according to the embodiment, NMP may be used as a solvent, PVdF or a PVdF copolymer may be used as a binder, and carbon black or acetylene black may be used as a conductive agent. In the positive electrode according to the embodiment, 94 wt % of the positive electrode active material, 3 wt % of the binder and 3 wt % of the conductive agent may be mixed to provide a mixture in a powder form, NMP is added to the mixture to prepare a slurry having a solid content of about 70 wt %, and the slurry may be coated, dried and pressed to prepare a positive electrode.
[0094] The thickness of the positive electrode collector may be in the range of about 3 μm to about 500 μm, or about 5 μm to about 300 μm, or about 10 μm to about 250 μm. The material used for the positive electrode collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the corresponding lithium battery. Examples of the positive electrode collector include stainless steel, aluminum, nickel, titanium, calcined carbon, aluminum or stainless steel surface treated with carbon, nickel, titanium or silver, or a combination thereof. The surface of the positive electrode collector may have a fine uneven structure to increase the bonding force between the positive electrode collector and the positive active material. The positive electrode collector may have a variety of shapes such as any of a film, sheet, foil, mesh, porous, foam or non-woven shape.
[0095] The loading level of the positive electrode active material composition may be, for example, about 30 mg / cm2 (mg / cm 2 ) or greater, about 35 mg / cm 2 or greater, or about 40 mg / cm 2 or greater. The cathode density may be, for example, about 3 grams per cubic centimeter (g / cc) or greater, or about 3.5 g / cc or greater, or about 4 g / cc or greater. A cathode having a high energy density may have a density of about 35 mg / cm 2 To about 50mg / cm 2 The positive electrode is a positive electrode plate in which both surfaces are coated with the positive electrode active material composition at a loading level of 37 mg / cc and has a positive electrode density of 3.6 g / cc.
[0096] When the loading level and the positive electrode density of the positive electrode active material composition satisfy the above ranges, the lithium battery including the positive electrode active material can exhibit a cell energy density of about 500 Wh / L or greater. In the lithium battery, the DCIR increase rate after 200 charge / discharge cycles at 45 °C can be about 20% or less.
[0097] Next, a negative electrode is prepared.
[0098] For example, a negative electrode active material, a conductive agent, a binder, and a solvent are mixed to prepare a negative electrode active material composition. In some embodiments, the negative electrode active material composition can be directly coated on a metal current collector and dried to prepare a negative electrode plate. In some embodiments, the negative electrode active material composition can be cast on a separate carrier to form a negative electrode active material film, and then it can be separated from the carrier and laminated on a metal current collector to prepare a negative electrode plate. The shape of the negative electrode is not limited thereto, and the negative electrode can have various shapes.
[0099] Examples of the negative electrode active material can be a silicon-based material, silicon oxide (SiO x , where 0 < x < 2), or a composite of a silicon-based material and a carbon-based material. For example, the silicon-based material can be silicon nanoparticles. Here, the size of the silicon nanoparticles can be 300 nm or less or, for example, in the range of about 10 nm to about 250 nm. As described above, the term "size" means the average diameter when the silicon particles are spherical or the average length scale when the silicon particles are non-spherical.
[0100] When the size of the silicon particles is within the above range, the life characteristics of the lithium battery can be excellent. Therefore, when using the electrolyte according to the embodiment, the life of the lithium secondary battery can be further improved.
[0101] Examples of the conductive agent include crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as natural graphite or artificial graphite having an amorphous, plate, sheet, spherical, or fibrous form. Examples of the amorphous carbon include soft carbon (carbon sintered at low temperature), hard carbon, mesophase pitch carbide, sintered coke, or a combination thereof.
[0102] The composite of the silicon-based material and the carbon-based material may be, for example, a composite having a structure including silicon particles arranged (coated) on graphite or a composite including silicon particles arranged on and inside graphite. For example, the composite may be an active material in which Si primary particles having an average particle size of about 200nm or less or, for example, in the range of about 100nm to about 200nm, or 150nm are arranged on graphite particles and then coated with a carbon-based material, or an active material in which silicon particles are arranged on and inside graphite. These composites can be obtained by product name "SCN1" (Si particles on graphite) or "SCN2" (Si particles inside and on graphite). SCN1 is an active material obtained by dispersing silicon particles having an average particle size of about 150nm on graphite particles and carbon coating the resulting particles. SCN2 is an active material including silicon particles having an average particle size of about 150nm on and inside graphite.
[0103] The negative electrode active material may include any suitable material that can be used as a negative electrode active material other than the above-mentioned negative electrode active materials.
[0104] Examples of other negative electrode active materials may include Si, Sn, Al, Ge, Pb, Bi, Sb, Si-Y alloy (wherein Y is an alkali metal, an alkaline earth metal, an element from Group 13 to Group 16, a transition metal, a rare earth element, or a combination thereof, and Y is not Si), Sn-Y alloy (wherein Y is an alkali metal, an alkaline earth metal, an element from Group 13 to Group 16, a transition metal, a rare earth element, or a combination thereof, and Y is not Sn), or a combination thereof. In some embodiments, Y may include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), scandium (Sc), yttrium (Y), titanium (Ti), zirconium (Zr), hafnium (Hf), (Rf), vanadium (V), niobium (Nb), tantalum (Ta), (Db), chromium (Cr), molybdenum (Mo), tungsten (W), (Sg), technetium (Tc), rhenium (Re), (Bh), iron (Fe), lead (Pb), ruthenium (Ru), osmium (Os), The metal oxide that can be used as another negative electrode active material can be lithium titanium oxide, vanadium oxide, or lithium vanadium oxide.
[0105] The conductive agent and binder used in preparing the negative active material composition may be the same as those used in preparing the positive active material composition, and may be at least one of the conductive agent and binder used in preparing the positive active material composition.
[0106] The amounts of the negative electrode active material, the conductive agent, the binder and the solvent can be determined by those skilled in the art without undue experimentation. Depending on the desired use and structure of the lithium battery, at least one of the conductive agent, the binder and the solvent may be omitted.
[0107] In the negative electrode active material composition, water may be used as a solvent. In the negative electrode according to the embodiment, water may be used as a solvent; carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), acrylate-based polymers and / or methacrylate-based polymers, and alginate (AG) may be used as binders; and carbon black, acetylene black and / or graphite may be used as a conductive agent. In the negative electrode according to the embodiment, 94% by weight of the negative electrode active material, 3% by weight of the binder, and 3% by weight of the conductive agent may be combined together as a mixture in powder form, water is added to the mixture to prepare a slurry having a solid content of about 70% by weight, and the slurry may be coated, dried, and pressed to prepare a negative electrode.
[0108] The thickness of the negative electrode current collector may be in the range of about 3 μm to about 50 μm, or about 5 μm to about 40 μm, or about 7 μm to about 35 μm. The material used as the negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the corresponding lithium battery. Examples of the negative electrode current collector include copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium or silver, aluminum-cadmium alloy, or a combination thereof. Like the positive electrode current collector, the negative electrode current collector may have a fine uneven structure on its surface to increase the bonding force between the current collector and the negative electrode active material. The negative electrode current collector may have a variety of shapes such as a film, sheet, foil, mesh, porous, foam or non-woven shape.
[0109] The loading level of the negative electrode active material composition may be determined according to the loading level of the positive electrode active material composition. For example, the loading level of the negative electrode active material composition may be about 12 mg / cm 2 or greater, about 15 mg / cm 2 or greater, about 18 mg / cm 2 or greater, or about 21 mg / cm 2or greater, per gram (g) of the negative electrode active material composition (i.e., 1 gram (g) of the composition without solvent). The negative electrode density may be, for example, about 1.5 g / cc or greater, or about 1.6 g / cc or greater, or about 1.7 g / cc or greater. The negative electrode where energy density is important may have a negative electrode density in the range of about 1.65 g / cc to about 1.9 g / cc.
[0110] When the loading level of the negative electrode active material composition and the electrode density are within these ranges, a battery including the negative electrode active material may exhibit a high unit cell energy density of 500 Wh / L or more.
[0111] Next, a separator is prepared and disposed between the positive electrode and the negative electrode.
[0112] The separator for the lithium battery may be any separator suitable for a lithium battery. In some embodiments, the separator may have low resistance to ion migration in the electrolyte and have excellent electrolyte retention capacity. Examples of the separator include glass fiber, polyester, Teflon TM , polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, each of which can be used as a nonwoven or woven fabric. For example, a windable separator including polyethylene or polypropylene can be used in a lithium ion battery. A separator having good organic electrolyte solution retention capacity can be used in a lithium ion polymer battery.
[0113] For example, the separator can be manufactured as follows.
[0114] In some embodiments, a polymer resin, a filler, and a solvent may be mixed together to prepare a separator composition. The separator composition may then be directly coated on an electrode and dried to form the separator. In some embodiments, the separator composition may be cast on a support and then dried to form a separator film, which may then be separated from the support and laminated on an electrode to form the separator.
[0115] The polymer resin used to make the separator may be any material suitable for use as a binder for an electrode plate. Examples of the polymer resin include vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, or a combination thereof.
[0116] The organic electrolyte solution may be provided as an electrolyte between the positive electrode and the negative electrode.
[0117] The electrolyte according to the embodiment may further include a nonaqueous electrolyte solution, an organic solid electrolyte, and / or an inorganic solid electrolyte, in addition to the organic electrolyte solution.
[0118] Examples of the organic solid electrolyte may include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers including ion dissociative groups, or combinations thereof.
[0119] Examples of the inorganic solid electrolyte may include Li 3 N, LiI, Li 5 NI 2 , Li 3 N-LiI-LiOH, Li 2 SiS 3 , Li 4 SiO 4 , Li 4 SiO 4 -LiI-LiOH, Li 3 PO 4 -Li 2 S-SiS 2 , or a combination thereof.
[0120] Reference Figure 1 , the lithium battery 1 includes a positive electrode 3, a negative electrode 2, and a separator 4. In some embodiments, the positive electrode 3, the negative electrode 2, and the separator 4 may be wound or folded, and then housed in a battery case 5. In some embodiments, the battery case 5 may be filled with an organic electrolyte solution and sealed with a cap assembly 6, thereby completing the manufacture of the lithium battery 1. In some embodiments, the battery case 5 may be cylindrical, rectangular, or thin-film. For example, the lithium battery 1 may be a large-size thin-film battery. In some embodiments, the lithium battery 1 may be a lithium-ion battery.
[0121] In some embodiments, the separator may be disposed between the positive electrode and the negative electrode to form a battery assembly. In some embodiments, the battery assembly may be stacked in a bi-unit battery structure and impregnated with an electrolyte solution. In some embodiments, the resulting assembly may be placed in a bag and hermetically sealed, thereby completing the manufacture of a lithium ion polymer battery.
[0122] In some embodiments, multiple battery assemblies may be stacked to form a battery pack, which may be used in any device that benefits from high capacity and high output, such as in a laptop computer, a smart phone, or an electric car.
[0123] In a lithium battery according to another embodiment, a DCIR increase rate may be significantly reduced compared to a lithium battery including a general nickel-rich lithium nickel composite oxide as a positive electrode active material, and thus the lithium battery may exhibit excellent battery characteristics.
[0124] The driving voltage of a lithium battery using a positive electrode, a negative electrode and an electrolyte may have, for example, a lower limit in the range of about 2.5 volts (V) to about 2.8 V and an upper limit in the range of about 4.1 V to about 4.4 V, and the lithium battery may have an energy density of about 500 Wh / L or more.
[0125] Examples of devices using the lithium battery include: power tools driven by electric motors; electric vehicles such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs); electric two-wheeled vehicles such as electric bicycles and electric scooters; electric golf carts; and power storage systems. However, embodiments of the device are not limited thereto.
[0126] As used herein, the term "alkyl" refers to a fully saturated branched or unbranched (straight chain or linear) aliphatic hydrocarbon group having the specified number of carbon atoms.
[0127] Examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, 3-methylhexyl, 2,2-dimethylpentyl, 2,3-dimethylpentyl and n-heptyl.
[0128] At least one hydrogen atom of the alkyl group may be replaced by a C1-C20 alkyl group substituted by a halogen atom (e.g., C 3 , CHF 2 , CH 2 F, or CCl 3 ), C1-C20 alkoxy, C2-C20 alkoxyalkyl, hydroxy, nitro, cyano, amino, amidino, hydrazine, hydrazone, carboxyl or its salt, sulfonyl, sulfamoyl, sulfonic acid or its salt, phosphate or its salt, C1-C20 alkyl, C2-C20 alkenyl, C2-C20 alkynyl, C1-C20 heteroalkyl, C6-C20 aryl, C7-C20 aralkyl, C6-C20 heteroaryl, C7-C20 heteroaralkyl, C6-C20 heteroaryloxy, C6-C20 heteroaryloxyalkyl, or C6-C20 heteroaralkyl.
[0129] As used herein, the term "cycloalkyl" refers to a monovalent group having one or more saturated rings in which all ring members are carbon.
[0130] As used herein, the term "halogen" refers to one of the elements of Group 17 of the periodic table (eg, fluorine, bromine, chlorine, iodine, and astatine).
[0131] As used herein, term " alkoxy " refers to the alkyl (that is, alkyl-O-) connected via oxygen, and the alkyl is identical with above definition. The example of the alkoxy may include methoxyl, ethoxy, propoxy, 2-propoxy, butoxy, tert-butoxy, pentyloxy and hexyloxy. At least one hydrogen atom of the alkoxy may be replaced by the substituent described above about the alkyl.
[0132] As used herein, the term "alkenyl" refers to a branched or unbranched hydrocarbon group having at least one carbon-carbon double bond. Examples of the alkenyl group may include vinyl, allyl, butenyl, propenyl, isobutenyl, and at least one hydrogen atom of the alkenyl group may be replaced by the substituent described above for the alkyl group.
[0133] As used herein, the term "alkynyl" refers to a branched or unbranched hydrocarbon group having at least one carbon-carbon triple bond. Examples of the alkynyl group may include ethynyl, butynyl, isobutynyl, and isopropynyl. At least one hydrogen atom of the alkynyl group may be replaced by a substituent described above for the alkyl group.
[0134] As used herein, the term "aryl" refers to a cyclic moiety in which all ring members are carbon and at least one ring is aromatic, the moiety having a specified number of carbon atoms. Examples of the aryl group may include phenyl, naphthyl, and tetrahydronaphthyl. Furthermore, at least one hydrogen atom of the aryl group may be replaced by a substituent described above for the alkyl group.
[0135] As used herein, the term "heteroaryl" refers to a monocyclic or bicyclic aromatic group in which at least one ring member is a heteroatom. The heteroatom is independently N, O, P and S, and the remaining ring atoms are carbon atoms. The heteroaryl may include, for example, 1-5 heteroatoms and 5-10 ring members. S or N may be oxidized to a variety of oxidation states. The heteroaromatic ring may optionally be fused to one or more aryl, alicyclic or heterocyclic rings.
[0136] Examples of the heteroaryl group may include thienyl, furyl, pyrrolyl, imidazolyl, pyrazolyl, thiazolyl, isothiazolyl, 1,2,3- Oxazolyl, 1,2,4- Oxazolyl, 1,2,5- Oxazolyl, 1,3,4- oxadiazole, 1,2,3-thiadiazolyl, 1,2,4-thiadiazolyl, 1,2,5-thiadiazolyl, 1,3,4-thiadiazolyl, isothiazol-3-yl, isothiazol-4-yl, isothiazol-5-yl, Oxazol-2-yl, Oxazol-4-yl, oxazol-5-yl, isoxazol-5-yl Oxazol-3-yl, iso Oxazol-4-yl, iso oxazol-5-yl, 1,2,4-triazol-3-yl, 1,2,4-triazol-5-yl, 1,2,3-triazol-4-yl, 1,2,3-triazol-5-yl, tetrazolyl, pyridin-2-yl, pyridin-3-yl, 2-pyrazin-2-yl, pyrazin-4-yl, pyrazin-5-yl, 2-pyrimidin-2-yl, 4-pyrimidin-2-yl, and 5-pyrimidin-2-yl.
[0137] Hereinafter, one or more embodiments will be described in detail with reference to the following examples and comparative examples. These examples are not intended to limit the purpose and scope of the one or more embodiments.
[0138] Example
[0139] (Preparation of organic electrolyte solution)
[0140] Example 1: 1.15M LiPF 6 and 1 wt% FPPA1
[0141] The compound represented by Formula 16a (fluoroethylene carbonate; FEC), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) were mixed in a volume ratio of 5:20:35:40 to prepare a non-aqueous organic solvent. 1.5 wt % of the compound represented by Formula 17a (vinyl carbonate; VC), 0.3 wt % of the compound represented by Formula 19a (maleic anhydride; MA), 0.2 wt % of the compound represented by Formula 21a (methylene dimethyl sulfonate; MMDS) and 1 wt % of the fluorine-containing phosphate compound represented by Formula 5 (FPPA1) were each added to the non-aqueous organic solvent, and 1.15 M LiPF 6 As lithium salt to prepare organic electrolyte solution.
[0142]
[0143] Example 2: 1.15M LiPF 6 and 1 wt% FPPA2
[0144] An organic electrolyte solution was prepared in the same manner as in Example 1, except that 1 wt % of the fluorine-containing phosphate compound (FPPA2) represented by Formula 10 was used instead of 1 wt % of the compound represented by Formula 5.
[0145]
[0146] Example 3: 1.15M LiPF 6 and 2 wt% FPPA2
[0147] An organic electrolyte solution was prepared in the same manner as in Example 1, except that 2 wt % of the fluorine-containing phosphate compound represented by Formula 10 (FPPA2) was used instead of 1 wt % of the fluorine-containing phosphate compound represented by Formula 5.
[0148]
[0149] Comparative Example 1: 1.15M LiPF 6 No additives
[0150] An organic electrolyte solution was prepared in the same manner as in Example 1, except that the fluorine-containing phosphoric acid ester compound represented by Formula 5 was not added.
[0151] Comparative Example 2: 1.15M LiPF 6 and 2 wt% TFEP
[0152] An organic electrolyte solution was prepared in the same manner as in Example 1, except that 2 wt % of the compound represented by Formula 25 was used instead of 1 wt % of the compound represented by Formula 5.
[0153]
[0154] Comparative Example 3: 1.15M LiPF 6 and 2 wt% TFPP
[0155] An organic electrolyte solution was prepared in the same manner as in Example 1, except that 2 wt % of the fluorine-containing phosphate compound represented by Formula 26 was used instead of 1 wt % of the fluorine-containing phosphate compound represented by Formula 5.
[0156]
[0157] Example 4: 1.15M LiPF 6 and 1 wt% FPPA2
[0158] The compound (FEC) represented by Formula 16a, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) were mixed in a volume ratio of 5:20:35:40 to prepare a non-aqueous organic solvent. 1.5 wt % of the compound (VC) represented by Formula 17a and 1 wt % of the fluorine-containing phosphate compound (FPPA2) represented by Formula 10 were each added to the non-aqueous organic solvent, and 1.15 M LiPF 6 As lithium salt to prepare organic electrolyte solution.
[0159]
[0160] Example 5: 1.15M LiPF 6and 1 wt% FPPA4
[0161] An organic electrolyte solution was prepared in the same manner as in Example 4, except that 1 wt % of the fluorine-containing phosphate compound represented by Formula 15 (FPPA4) was used instead of 1 wt % of the fluorine-containing phosphate compound represented by Formula 10.
[0162]
[0163] Comparative Example 4: 1.15M LiPF 6 and 1 wt% TMP
[0164] An organic electrolyte solution was prepared in the same manner as in Example 1, except that 1 wt % of the compound represented by Formula 27 (trimethyl phosphate; TMP) was used instead of 1 wt % of the fluorine-containing phosphate compound represented by Formula 10.
[0165]
[0166]
[0167] Comparative Example 5: 1.15M LiPF 6 and 1 wt% TEP
[0168] An organic electrolyte solution was prepared in the same manner as in Example 4, except that 1 wt % of the compound represented by Formula 28 (triethyl phosphate; TEP) was used instead of 1 wt % of the fluorine-containing phosphoric acid ester compound represented by Formula 10.
[0169]
[0170] Comparative Example 6: 1.15M LiPF 6 and 1 wt% TFPP
[0171] An organic electrolyte solution was attempted to be prepared in the same manner as in Example 4, except that 1 wt % of the compound represented by Formula 29 was used instead of 1 wt % of the fluorine-containing phosphoric acid ester compound represented by Formula 5.
[0172] The compound represented by Formula 29 was not dissolved in the organic solvent but precipitated, and thus preparation of an organic electrolyte solution was impossible.
[0173]
[0174] (Preparation of lithium battery (full cell))
[0175] Example 6: Preparation of lithium secondary battery (full unit cell), carbon-silicon composite negative electrode (SCN)
[0176] (Preparation of positive electrode)
[0177] 95.0 wt% of LiNi as the positive electrode active material 0.88 Co 0.10 Mn 0.02 O 2 , 2.5 wt % of Denka black as a conductive agent, and 2.5 wt % of PVDF (Solef 6020, available from Solvay) as a binder were mixed to prepare a mixture. The mixture was added to N-methyl-2-pyrrolidone (NMP) as a solvent so that the solid content was 60%, and the solid was dispersed in the solvent for 30 minutes by using a mechanical stirrer to prepare a positive electrode active material composition. The positive electrode was coated with 37 mg / cm 2 The positive electrode active material composition was double-sidedly coated on an aluminum foil current collector having a thickness of 12 μm at a loading level of , dried in a hot air dryer at 100° C. for 0.5 hour, further dried at 120° C. in a vacuum for 4 hours, and roll-pressed to prepare a positive electrode in which a positive electrode active material layer having a density of 3.6 g / cc was formed on the current collector.
[0178] (Preparation of negative electrode)
[0179] 97 wt % of a mixture prepared as follows (85 wt % of graphite powder (MC20, 99.9% or higher purity, available from Mitsubishi Chemical) as a negative electrode active material and about 15 wt % of a carbon-silicon composite (available from BTR) in which a composite of carbon particles and silicon nanoparticles is formed by mechanochemically so that silicon nanoparticles are on and in graphite) and 3 wt % of an alginate (AG) binder as a binder were mixed. The mixture was added to water as a solvent so that the solid content was 50%, and the solid was dispersed in the solvent by using a mechanical stirrer for 60 minutes to prepare a negative electrode active material composition. The mixture was coated with 21.87 mg / cm 2 The negative electrode active material composition was double-sided coated on a copper foil current collector having a thickness of 10 μm at a loading level of 100° C., dried in a hot air dryer at 100° C. for 0.5 hours, dried in a vacuum at 120° C. for another 4 hours, and roll-pressed to prepare a negative electrode in which a negative electrode active material layer having a density of 1.65 g / cc was formed on the current collector. The average particle size of the silicon nanoparticles in the carbon-silicon composite was about 150 nm, and the average diameter of the secondary particles of the carbon-silicon composite was about 5 μm.
[0180] (Assembly of lithium batteries)
[0181] A 18650 cylindrical lithium battery was prepared using the positive and negative electrodes thus prepared, a polyethylene separator, and the electrolyte solution prepared in Example 1 as an electrolyte solution.
[0182] Examples 7 and 8
[0183] A lithium battery was prepared in the same manner as in Example 6, except that the organic electrolyte solutions prepared in Examples 2 and 3 were each used instead of the organic electrolyte solution prepared in Example 1.
[0184] Comparative Examples 7-9
[0185] Lithium batteries were prepared in the same manner as in Example 6, except that the organic electrolyte solutions prepared in Comparative Examples 1 to 3 were each used instead of the organic electrolyte solution prepared in Example 1.
[0186] Example 9: Preparation of lithium secondary battery (full unit cell), graphite (Gr) negative electrode
[0187] A lithium battery was prepared in the same manner as in Example 6, except that graphite powder (MC20, 99.9% or higher purity, available from Mitsubishi Chemical) was used instead of the mixture as the negative electrode active material, and the organic electrolyte solution prepared in Example 4 was used instead of the organic electrolyte solution prepared in Example 1.
[0188] Example 10
[0189] A lithium battery was prepared in the same manner as in Example 9, except that the organic electrolyte solution prepared in Example 5 was used instead of the organic electrolyte solution prepared in Example 4.
[0190] Comparative Examples 10 and 11
[0191] A lithium battery was prepared in the same manner as in Example 9, except that the organic electrolyte solutions prepared in Comparative Examples 4 and 5 were each used instead of the organic electrolyte solution prepared in Example 4.
[0192] Evaluation Example 1: Evaluation of charge / discharge characteristics at high temperature (45° C.)
[0193] At 45°C, the lithium batteries prepared in Examples 6-8 and Comparative Examples 7-9 were each charged at a constant current of 0.2C until the voltage was 3.6V (relative to Li), and then discharged at a constant current of 0.2C until the discharged voltage was 2.8V (relative to Li) (the first cycle of the formation process).
[0194] At 45°C, the lithium batteries undergoing the first cycle of the formation process were each charged at a constant current of 0.2C rate until the voltage was 4.3V (relative to Li), and discharged at a constant current of 0.2C rate until the discharged voltage was 2.8V (relative to Li) (the second cycle of the formation process).
[0195] At 45°C, the lithium batteries undergoing the second cycle of the formation process were each charged at a constant current of 0.5C rate until the voltage was 4.3V (relative to Li), and the current was cut off at 0.05C rate while the voltage was maintained at 4.3V in a constant voltage mode (CV mode). Then, the battery was discharged at a constant current of 1.0C rate until the discharged voltage was 2.8V (relative to Li). (The third cycle of the formation process).
[0196] At 45°C, the lithium batteries undergoing the formation process were each charged at a constant current of 0.5C rate until the voltage was 4.3V (relative to Li), and the current was cut off at 0.05C rate while the voltage was maintained at 4.3V in CV mode. Then, the battery was discharged at a constant current of 1.0C rate until the discharged voltage was 2.8V (relative to Li). This cycle was repeated 200 times.
[0197] Throughout the charge / discharge cycle, a holding time of 10 minutes was set after each charge / discharge cycle.
[0198] Some charge / discharge test results are shown in Table 1. The capacity retention rate at the 200th cycle is defined as shown in Equation 1.
[0199] Equation 1
[0200] Capacity retention rate at the 200th cycle [%] = [discharge capacity at the 200th cycle / discharge capacity at the 1st cycle] × 100%
[0201] Table 1
[0202] Carbon-silicon composite anode Capacity retention rate [%] Example 6 (FPPA1, 1 wt%) 78.2 Example 7 (FPPA2, 1 wt%) 78.0 Example 8 (FPPA2, 2 wt%) 78.6 Comparative Example 7 (no additive) 77.4 Comparative Example 8 (TFEP, 2 wt%) 67.4
[0203] As shown in Table 1, the lithium batteries of Examples 6-8 using an organic electrolyte solution using a fluorine-containing phosphate compound containing a phenyl group not substituted by fluorine have improved life characteristics at high temperatures compared to the lithium battery of Comparative Example 7 not including an additive and the lithium battery of Comparative Example 8 using an organic electrolyte solution using a fluorine-containing alkyl-based phosphate compound. Moreover, compared to the life characteristics of the lithium battery of Comparative Example 9, the lithium batteries of Examples 6-8 have improved life characteristics at high temperatures.
[0204] As shown in Table 1 of WO 2006 / 016733, which is incorporated herein by reference, trifluoroethyl phosphate (TFEP) exhibits improved lifetime characteristics relative to trifluorophenyl phosphate (TFPP).
[0205] The energy density of the lithium battery prepared in Example 6 is 710Wh / L.
[0206] Evaluation Example 2: Evaluation of DC internal resistance (DC-IR) at room temperature (45°C)
[0207] The direct current internal resistance (DC-IR) of the lithium batteries prepared in Examples 6-8 and Comparative Examples 7-9 at high temperature (45° C.) was evaluated for the lithium batteries before high temperature charging (0 cycle or in the initial state) and after 200 charge / discharge cycles as follows.
[0208] In the first cycle, each battery was charged at a constant current of 0.5 C rate to a voltage of 50% of the state of charge (SOC), and the current was cut off at a rate of 0.02 C. Then, the battery was left to stand for 10 minutes.
[0209] After discharging at a constant current of 0.5 C rate for 30 seconds, the batteries were each left to stand for 30 seconds, charged at a constant current of 0.5 C rate for 30 seconds, and left to stand for 10 minutes.
[0210] After discharging at a constant current of 1.0 C rate for 30 seconds, the batteries were each left to stand for 30 seconds, charged at a constant current of 0.5 C rate for 1 minute, and left to stand for 10 minutes.
[0211] After discharging at a constant current of 2.0 C rate for 30 seconds, the batteries were each left to stand for 30 seconds, charged at a constant current of 0.5 C rate for 2 minutes, and left to stand for 10 minutes.
[0212] After discharging at a constant current of 3.0 C rate for 30 seconds, the batteries were each left to stand for 30 seconds, charged at a constant current of 0.5 C rate for 2 minutes, and left to stand for 10 minutes.
[0213] The average voltage drop value for 30 seconds for each C rate is a DC voltage value. The DC resistance (DC-IR) was calculated from the measured DC voltage, and some results are shown in Table 2.
[0214] The DCIR increase rate was calculated according to Equation 2.
[0215] Equation 2
[0216] DCIR increase rate = [(DCIR after the 200th cycle - initial DCIR) / initial DCIR] × 100%
[0217] Table 2
[0218]
[0219] As shown in Table 2, compared with the DCIR increase rates of the lithium batteries prepared in Comparative Examples 7 and 8, the lithium batteries of Examples 6 to 8 had significantly reduced DCIR increase rates.
[0220] Evaluation Example 3: Evaluation of the amount of gas generated at high temperature (60°C)
[0221] At room temperature (25°C), the lithium batteries prepared in Examples 9 and 10 and Comparative Examples 10 and 11 were each charged at a constant current of 0.2C until the voltage was 3.6V, and discharged at a constant current of 0.2C until the discharged voltage was 2.8V (formation process, 1st cycle).
[0222] In the second cycle, at 25°C, the batteries undergoing the first cycle of the formation process were each charged at a constant current of 0.2C until the voltage was 4.3V (relative to Li); and discharged at a constant current of 0.2C until the discharged voltage was 2.8V (formation process, second cycle).
[0223] In the third cycle, each battery undergoing the second cycle of the formation process was charged at a constant current of 0.5C until the voltage was 4.3V (relative to Li); and the current was cut off at a rate of 0.05C while the voltage was maintained at 4.3V in a constant voltage mode (CV mode). Then, the battery was discharged at a constant current of 0.2C until the discharged voltage was 2.8V. (Formation process, third cycle).
[0224] In the 4th cycle, the batteries were each charged at a constant current of 0.5C rate until the voltage was 4.30V, and charged at a constant voltage until the current was 0.05C while the voltage was maintained at 4.30V. The charged batteries were stored in an oven at 60°C for 10 days, taken out of the oven, and discharged until the discharged voltage was 2.8V. The batteries were each placed in a fixture and exploded to measure the amount of gas generated by converting the internal gas pressure change into volume. Some results are shown in Table 3.
[0225] Table 3
[0226] Amount of gas produced [ml / g] Example 9 0.59 Example 10 0.60 Comparative Example 10 0.62 Comparative Example 11 0.64
[0227] As shown in Table 3, the lithium batteries of Examples 9 and 10 had reduced amounts of gas generation compared to the amounts of gas generation of the lithium batteries of Comparative Examples 10 and 11.
[0228] As described above, according to one or more embodiments, when a lithium battery includes an organic electrolyte solution including a fluorine-containing phosphate-based compound having an asymmetric structure, side reactions in the lithium battery may be suppressed and lifespan characteristics of the lithium battery may be improved.
[0229] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for purposes of limitation. Descriptions of features or aspects within each embodiment should be considered as available for other similar features or aspects in other embodiments.
[0230] Although one or more embodiments have been described with reference to the drawings, it will be understood by those of ordinary skill in the art that various changes in form and details may be made therein without departing from the spirit and scope as defined by the following claims.
Claims
1. An organic electrolyte solution, comprising: a lithium salt; an organic solvent; a fluorinated phosphate compound represented by one of Formula 4 - Formula 15 in an amount in the range of 0.01 wt% to 2.0 wt%; a compound represented by Formula 17a in an amount in the range of 0.1 wt% to 2.0 wt%; a compound represented by Formula 19a in an amount in the range of 0.1 wt% to 1.0 wt%; and a compound represented by Formula 21a in an amount in the range of 0.1 wt% to 1.0 wt%, wherein the wt% is based on the total weight of the organic electrolyte solution; and the organic solvent comprises a compound represented by Formula 16a in an amount in the range of 1 vol% to 10 vol%, based on the total volume of the organic solvent:
2. The organic electrolyte solution according to claim 1, wherein the amount of the fluorinated phosphate compound represented by one of Formula 4 - Formula 15 is in the range of 0.5 wt% to 2 wt%, based on the total weight of the organic electrolyte solution.
3. The organic electrolyte solution according to claim 1, wherein the organic solvent comprises at least one of the following: ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, propylene carbonate, ethylene carbonate, butylene carbonate, ethyl propionate, ethyl butyrate, acetonitrile, succinonitrile, adiponitrile, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, γ-valerolactone, γ-butyrolactone or tetrahydrofuran.
4. The organic electrolyte solution according to claim 1, wherein the lithium salt comprises at least one of the following: LiPF6, LiBF4, LiCF3SO3, Li(CF3SO2)2N, LiC2F5SO3, Li(FSO2)2N, LiC4F9SO3, LiN(SO2CF2CF3)2, or a compound represented by Formula 30 - Formula 33:
5. The organic electrolyte solution according to claim 1, wherein the concentration of the lithium salt is in the range of 0.01 molar concentration to 5.0 molar concentration.
6. A lithium battery, comprising: a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; and the organic electrolyte solution according to any one of claims 1 - 5 between the positive electrode and the negative electrode, wherein the positive electrode active material comprises a lithium transition metal oxide containing nickel and at least one transition metal other than nickel, and wherein the amount of nickel in the lithium transition metal oxide is 70 mol% or more, based on the total molar number of transition metals.
7. The lithium battery according to claim 6, wherein the lithium transition metal oxide is represented by Formula 22: Formula 22 Li a Ni x Co y M z O 2-b A b in, In Formula 22, 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.7 ≤ x < 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z = 1; M is at least one of manganese, vanadium, magnesium, gallium, silicon, tungsten, molybdenum, iron, chromium, copper, zinc, titanium, aluminum or boron; and A is at least one of F, S, Cl or Br.
8. The lithium battery according to claim 6, wherein the lithium transition metal oxide is a compound represented by at least one of Formula 23 or Formula 24: Formula 23 LiNi x Co y Mr z O2 Formula 24 LiNi x Co y Al z O2 in, In Formulas 23 and 24, 0.7 ≤ x ≤ 0.95, 0 < y ≤ 0.3, and 0 < z ≤ 0.
3.
9. The lithium battery according to claim 6, wherein the negative electrode active material includes at least one of a silicon-based material, a carbon-based material, a composite of a silicon-based material and a carbon-based material, or a silicon oxide.
10. The lithium battery according to claim 9, wherein the composite of the silicon-based material and the carbon-based material includes silicon nanoparticles.
11. The lithium battery according to claim 10, wherein the composite of the silicon-based material and the carbon-based material has a size in the range of 5 micrometers to 20 micrometers, and the silicon nanoparticles have a size of 200 nanometers or less.
12. The lithium battery according to claim 6, wherein the lithium battery has a capacity retention rate of 70% or more at 45°C measured after 200 charge / discharge cycles.
13. The lithium battery according to claim 6, wherein the lithium battery has a DC internal resistance increase rate of 20% or less at 45°C measured after 200 charge / discharge cycles.
14. The lithium battery according to claim 6, wherein the energy density per unit volume of each unit cell is 500 watt-hours per liter or more.
Citation Information
Patent Citations
Nonaqueous electrolyte for lithium secondary batteries, and lithium secondary batteries comprising the same
WO2006016733A1
Lithium-ion battery electrolyte and lithium ion battery with the same
CN106450438A
Electrolyte solution lithium and secondary battery containing electrolyte solution
CN106848381A
Phosphorus containing electrolytes
CN110915037A
Non-aqueous electrolyte, fire retardant therefor, and battery thereof
JP2005228683A